Actinomyces-associated calcifications around an impacted third molar of the mandible. Issue 3 (May 2017) - Shibasaki, Maiko; Iwai, Toshinori; Chikumaru, Hiroshi; Hirota, Makoto; Mitsudo, Kenji; Hibiya, Takashi; Ohashi, Kenichi; Tohnai, Iwai
Abstract: Actinomycosis is often considered an affliction of the soft tissues, but in fact, the process spreads to bone in up to 15% of cases. Although Actinomyces -associated lesions in the jaw, such as radicular cyst and osteomyelitis, have been reported by many authors, there are few reports have previously described Actinomyces -associated calcification in the jaw. We report here a rare case of Actinomyces -associated calcifications around an impacted third molar of the mandible. A 76-year-old man with left mandibular pericoronitis was referred to our department. A panoramic radiograph showed alveolar bone resorption caused by severe periodontitis of the left mandibular second molar and multiple small radiopaque spots around the crown of left mandibular third molar in a radiolucent lesion. Computed tomography revealed that the lesion of the left mandibular retromolar lesion was low density, with multiple high density spots surrounding the third molar crown surface. Removal of the lesion and the left mandibular second and third molars were performed and multiple small black pieces of hard tissue were present on the crown surface of the third molar. Histopathological examination of soft tissue specimen around the third molar revealed that collagenous fibroconnective tissue infiltrated by inflammatory cells with squamous epithelium on its surface. Black hard tissue consisted of calcification and conglomerations of Actinomyces which were densely stained by hematoxylin-eosin stain were observed at the margin of the hard tissue surrounding tiny filamentous structures. The postoperative course was uneventful without need for additional antibiotics and there has been no recurrence 22 months after surgery.